Personal financial planning: factors that affect the level of awareness among newly employed graduates at Scope International (M) Sdn Bhd / Mohd Firdzus Bakri - Bakri, Mohd Firdzus (Faculty of Business and Management, 2010)
This research project was conducted to identfy the factors that affect the awareness level on Personal Financial Planning among newly employed graduates at Scope International (M) Sdn Bhd. The purpose of this research is investigate the problems and suggest solution from literature and study done on the topic because the awareness level of newly employed graduates on personal financial planning is said to be low especially for those who lives in urban area like Kuala Lumpur. The researcher do literature review from the past researcher that are related to this study. The literature review helps to describe, summaries, evaluate, clarify and/or integrate the content of primary reports. Furthermore, the data methodology then, help the researcher to interpret the data from questionnaire that been distributed to convenient respondent. The methods use is Realibility Statistic (Cronbach’s alpha), Frequencies (demographic statistic), Descriptive statistic and Hypothesis Testing which consists of Pearson Correlation Matrix and t-Test for Differences between Two Groups. Conclusions and recommendations will come out after data been analyze.